Final answer:
To solve the equation 10x² - 6x = 0, factor out x to get x(10x - 6) = 0, yielding two solutions for x: 0 and 0.6.
Step-by-step explanation:
The given equation is 10x² - 6x = 0. To find the value of x, we can factor out x from the equation, which gives us x(10x - 6) = 0. This result yields two possible solutions for x because a product of factors equals zero if and only if at least one of the factors is zero.
So, we set each factor equal to zero and solve for x:
- x = 0
- 10x - 6 = 0, which simplifies to x = 6/10 or x = 0.6
Therefore, the values of x that satisfy the given equation are 0 and 0.6.